La ciudadanía activa desde la perspectiva del directivo, docente y estudiantes de una I.E. pública de Amazonas, Perú - Torres Chavarría, Luis (2023)
The purpose of this qualitative research was to analyze the perception of management, teachers and students about active citizenship in a public IE in Amazonas to describe their conceptualization, importance, purpose and characteristics of active citizens. The focus group and the interview were used to collect the information. It was processed with the inductive method through open and axial coding. The results show that active citizenship is membership in the political community, compliance with rules and participation in socio-political activities. Its development in schools is important to form citizens with socio-personal values. Its purpose is constructive interaction, participation in the community and knowledge of rights and duties. Active citizens are characterized by possessing socio-personal values, being agents of healthy coexistence and common good. The conclusions show that aspects of passive citizenship prevail in the narrative of the informants.